Population dynamics of Rattus argentiventer, Rattus losea, and Rattus rattus inhabiting a mixed-farming system in the Red River Delta, Vietnam - Brown, Peter R.; Tuan, Nguyen Phu; Singleton, Grant R.; Hue, Dao Thi; Hoa, Phung Thi; Ha, Phi Thi Thu; Tan, Tran Quang; Van Tuat, Nguyen (Wiley, 2005)
Rodent pests cause significant damage to lowland irrigated rice crops in the Red River Delta of northern Vietnam. Data from a 4‐year study were examined to look at the population dynamics of the ricefield rat, Rattus argentiventer (representing 50% of captures), the lesser ricefield rat, Rattus losea (30% of captures), and the black rat, Rattusrattus complex (9% of captures) that inhabit the irrigated mixed‐cropping system. We tested the hypothesis that these rodent species were breeding in response to the availability of high‐quality food provided by crops rather than in response to rainfall. The abundance of rodents fluctuated annually, with a main peak following the spring rice crop, and a secondary peak following the summer rice crop. There was a strong relationship between the monthly abundance of rats and rainfall, but a weak relationship between monthly rates of increase and rainfall. There were distinct peaks in breeding activity during the reproductive stages of the rice crops suggesting that changes in crop stages were more important than rainfall in this seasonal, but irrigated agroecosystem. The modal litter size for R. argentiventer was 8 (mean of 8.67±0.20 SE, range 2–16), where the mode for R. losea, was 7 (mean of 7.32±0.15 SE, range 3–14). Management of these species needs to be conducted prior to the onset of the main breeding seasons.